(untitled) (International Journal of Engineering and Computer Science, 2014)
A MANET contains wireless mobile nodes that communicate together without any need of infrastructure of network as well as any central base station. This is the reason it is widely used in area that has a limitation of infrastructure and even we can form huge group of people with fruitful communication through the use of mobile nodes in the MANET. Nodes in the MANETS are autonomous and managed by itself in the absence of infrastructure. Mobile ad-hoc networks are exposed to numerous attacks due to (a) dynamic behavior. (b) In MANETS, any node can join and leave the network at any time. Black node is a malicious node that drops the packets in the network by giving the false replay for any route request and also it does not contains any path for destination. The existing method identifies the black hole attack based upon the sequence number in the RREP message. Here the proposed method eradicates the malicious black hole node at distributed level. For the implementation of our methodology NS2 tool is used. The overall results by the simulation increases the detection rate of malicious node and that leads to the increase in network performance by lowering the rate of packet drop ratio.